Long‐chain fatty acids in sarcopenia patients with cardiovascular diseases: importance of n‐9 monounsaturated fatty acids. Issue 4 (28th July 2020) - Katoh, Atsushi; Ikeda, Hisao; Matsushima, Yoshihisa; Sasaki, Motoki; Okina, Norihito; Niiyama, Hiroshi; Harada, Haruhito; Nishiyama, Yasuhiro; Kai, Hisashi
Abstract: Background: Long‐chain fatty acids are essential components of the cellular energy supply, cellular membranes, and autacoid synthesis. It has been suggested that long‐chain fatty acids might be involved in the pathophysiology underlying sarcopenia. We investigated the association between sarcopenia and serum long‐chain fatty acid profile in patients with cardiovascular diseases. Methods: We retrospectively investigated 308 cardiovascular patients [age: 72 ± 12 (mean ± SD), 174 male patients] admitted to our hospital. All patients were evaluated by sarcopenia diagnostic tests and serum free fatty acid analyses. Results: Seventy‐seven patients (25%) were diagnosed with sarcopenia. Serum fatty acid weight percentages of nervonic acid and erucic acid were elevated in patients with sarcopenia compared with those without. Nervonic acid, which was an independent factor for sarcopenia in binary logistics regression analysis ( B  = 2.559, p  < 0.001), correlated negatively with skeletal muscle index ( r  = −0.331, p  < 0.001), gait speed ( r  = −0.387, p  < 0.001), and handgrip strength ( r  = −0.372, p  < 0.001). These significant relationships were confirmed in subgroup analyses stratified by age and gender. In receiver operating characteristic curve analysis, the cut‐off of nervonic acid weight percentage for diagnosis of sarcopenia was 1.37% with a sensitivity and specificity of 76.6% and 65.1%, respectively. Conclusions: Nervonic acid, an n‐9 monounsaturated fatty acid, might serve as a new marker for sarcopenia in patients with cardiovascular diseases. Further studies with larger patient numbers will be needed to determine the roles of long‐chain fatty acids in sarcopenia.